Revestimentos a base de Ta/Al2O3 produzidos por aspersão térmica sobre substrato metálico - Mendes, Marcio Willians Duarte (2010)
Metal substrates were coated by thermal spraying plasma torch, they were positioned at a distance of 4 and 5 cm from the nozzle exit of the plasma jet. The starting materials were used for deposition of tantalum oxide powder and aluminium. These two materials were mixed and ground into high-energy mill, then immersed in the torch for the production of alumina coating infused with particles of tantalum with nano and micrometric size. The spraying equipment used is a plasma torch arc not transferred, which operating in the range of 250 A and 80 V, was able to produce enough heat to ignite aluminothermic between Ta2O5 and aluminum. Upon reaching the plasma jet, the mixing powders react with the heat of the blaze, which provides sufficient energy for melting aluminum particles. This energy is transferred through mechanisms of self-propagating to the oxide, beginning a reduction reaction, which then hits on the surface of the substrate and forms a coating on which a composite is formed by a junction metal - ceramic (Ta +Al2O3). The phases and quantification of each were obtained respectively by X-ray diffraction and the Rietveld method. Morphology by scanning electron microscopy and chemical analysis by energy dispersive spectroscopy EDS. It was also performed measurements of the substrate roughness, Vickers microhardness measurements in sprays and determination of the electron temperature of the plasma jet by optical emission spectroscopy EEO. The results confirmed the expectation generated around the end product of spraying the mixture Ta2O5 + Al, both in the formation of nano-sized particles and in their final form. The electron excitation temperature was consistent with the purpose of work, in addition, the thermodynamic temperature was efficient for the reduction process of Ta2O5. The electron excitation temperature showed values of 3000, 4500 and 8000 K for flows10, 20 and 30 l / min respectively, these values were taken at the nozzle exit of the plasma jet. The thermodynamic temperature around 1200 ° C, was effective in the reduction process of Ta2O5